PENGETAHUAN, APD, LAMA PENYEMPROTAN DAN KERACUNAN PESTISIDA PADA PEKERJA PENYEMPROT KELAPA SAWIT DI PT. HARLITAMA AGRI MAKMUR KABUPATEN KONAWE - Pitrah Asfian; Regitha Pricillia Cahyani Tambosisi (NHM PRESS, 2022)
Pesticides are toxic materials that have a detrimental impact on the body so that when in direct contact with pesticides it can cause acute and chronic poisoning. In humans, exposure to pesticides can be through several ways including through drinking, food, or work as well as through routes such as skin (dermal), respiratory (inhalation), or mouth (oral). The purpose of this study was to determine the description of knowledge, personal protective equipment and duration of spraying with pesticide poisoning in oil palm spraying workers at PT. Harlitama Agri Makmur Konawe Regency in 2021. This research is a quantitative descriptive study. The sample in this study is total sampling. totaling 63 people. The results of this study are pesticide poisoning in spraying workers at PT Harlitama Agri Makmur as many as 24 people have been poisoned. Knowledge of spraying workers at PT Harlitama Agri Makmur as many as 40 respondents had a low category. Personal protective equipment for spraying workers at PT Harlitama Agri Makmur as many as 40 respondents had an incomplete category. The duration of spraying on spraying workers at PT Harlitama Agri Makmur was 46 respondents in the good category.